Elektronisk snuing av Stor norsk-fransk ordbok - Jacobsen, Tove (Nordiske Studier i Leksikografi, 1995)
The Large Norwegian-French Dictionary is computer-readable and coded, and as such it is especially suited as a basis for other projects. By reversing the dictionary by computer, it serves as a base for a French-Norwegian dictionary, and, in this manner the material from an active dictionary is transposed toa passive one. In this paper, the results of the reversing of the dictionary are described, and the effectiveness and quality obtained by such a method are discussed.